SARS-CoV-2 viral shedding in vaccinated and unvaccinated persons: A case series. Issue 11 (10th March 2023) - McCormick, David W.; Hagan, Liesl M.; Salvatore, Phillip P.; Magleby, Reed; Lee, Christine; Sleweon, Sadia; Nicolae, Lavinia; Dixon, Tom; Banta, Robert; Ogle, Isaac; Young, Cristen; Dusseau, Charles; et al.
Abstract: The preclinical time course of SARS-CoV-2 shedding is not well-described. Understanding this time course will help to inform risk of SARS-CoV-2 transmission. During an outbreak in a congregate setting, we collected paired mid-turbinate nasal swabs for antigen testing and reverse-transcription polymerase chain reaction (RT-PCR) every other day from all consenting infected and exposed persons. Among 12 persons tested prospectively before and during SARS-CoV-2 infection, ten of 12 participants (83%) had completed a primary COVID-19 vaccination series prior to the outbreak. We recovered SARS-CoV-2 in viral culture from 9/12 (75%) of participants. All three persons from whom we did not recover SARS-CoV-2 in viral culture had completed their primary vaccination series. We recovered SARS-CoV-2 from viral culture in 6/9 vaccinated persons and before symptom onset in 3/6 symptomatic persons. These findings underscore the need for both non-pharmaceutical interventions and vaccination to mitigate transmission.